Conexões entre design, economia solidária e tecnologia social na perspectiva do campo CTS - Santos, Isadora Candian dos (2017)
Within the context of developing solutions to reduce social inequalities, the themes of design, solidarity economy and social technology present the interfaces: the seek to overcome poverty and promote socioeconomic development, with environmental preservation and collective management. From this starting point, this research sought to understand the relations between design, solidarity economy and social technology, to identify points of approximation and limitations between the themes, and to contribute to the common understanding between the themes and their fields. Based on design as a field of studies and practices, this work focused on the production of knowledge associated with praxis, aiming to understand the relations between design, solidarity economy and social technology, seeking researches with practical experiences, through their scientific productions and their certified social technologies. With this object, this work had four stages of research, characterized by quantitative and qualitative approaches, using the categorical content analysis method: approximations of the conceptual and historical bases of the three themes; survey of researches with practical experiences; selection of five researches with practical experiences and ten qualitative interviews with authors and co-authors; and, analysis and systematization of the data collected. The results of the first stage brought elements for the discussion and basis for the categorizations, problematizing common aspects: historical and sociological contexts - Industrial Revolution and Cold War; motivations - questioning about consumption, forms of production and technological development; participatory and democratic methodologies of work; methods of propagation – collective property and free intellectual property; and, final objectives - promotion of social changes and principles that aim at sustainability. And, as limitations and divergences: possible contradictions about the collective construction of knowledge; the understanding of design from an deterministic perspective of science and technology; and, the limitations of promoting changes inside the capitalist system. The second stage of research led to the survey of 46 researches with practical experiences among the accepted results, covering the period of 2003 and 2015. The third stage selected 5 of these results and 10 interviews were conducted with authors and coauthors, addressing the central concepts of this work and related concepts: social design, design and sustainability, solidarity economy and social technology. The fourth and last stage analyzed and systematized the data collected and pointed to the final results of this work: the understanding of possible relations between the concepts of social design, design and sustainability, solidarity economy and social technology, which were understood as a mean, as an end and also in a transverse way, pointing to a diffuse understanding. However, it was possible to point out a transverse element, understood as the common objective of the themes: promoters of sustainability, seekers of the sustainable development, in its four axes - economic, social, environmental and institutional / cultural. And, finally, it was possible to point for future development of the themes, such as scientific research, public policies, projects and / or practical actions.